Decision Analysis of Vessel Re-Flagging: Case Study of PT Hallin Marine Indonesia - Wardianthi, Renni Puri; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2013)
The underwater inspection services performed by the subsea contractor to support offshore operations in oil and gas industry which is currently depends on foreign companies due to the resources and equipment were not available in Indonesia.  Lack of equipment and resources domestically contrary to the need the underwater inspection skills and dominated by foreign companies and foreign workers the government issued a policy to discontinue the use of foreign flag vessels including foreign workers who work on-board the vessel in Indonesia in accordance with the principle of cabotage to optimize local resources which will implement in early 2013 for several types of vessels operating in Indonesian waters. A contribution towards to support the Government regulations tailored to the needs of the market for diving support vessels to do the underwater services, Hallin intends to revamp its vessel into the Indonesian flagged vessel. This paper will determine the best option which vessel suitable to be re-flagged in-line with the cabotage principle as the bottom regulation for Indonesian water transportation regulation. The analysis of vessel determination will be conducted using a SMART analysis and Basic Patterns of Thinking in the Organization Context such as Situation Appraisal, Problem Analysis, Decision Analysis and Potential Problem Analysis get a suitable vessel to be re-flagged tailored with the questionnaires given to the clients, it is expected to receive a feedback and determining the type of a suitable vessel, the process of implementation and application to re-flagged.   Keywords: Decision Analysis, Cabotage Policy, Diving Support Vessel, SMART Analysis, Problem Analysis, Situational Analysis and Potential Problem Analysis.